A method to obtain 3D kinematics data of whole high jump movement - Ai, K. W.; Yu, H. B. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to introduce how to use 3D image analysis with Pan/Tilt/Zoom cameras to obtain the 3D kinematical data in the event of high jump. The attempts by a chinese elite female highjumper were filmed with two cameras. In addition to control frame, the 3D coordinates of additional control points were measured by a theodolite and transformed into the same reference system. Then these parameters were used in the Motion Analysis System and in the software to level the reference system. Finally, the 3D kinematical data of whole high jump movement could be obtained for further analyzing techniques. This method can be used to analyze other sport events.